Reconfigurable Hairpin Bandpass Filter for Wireless Applications - Krishna Chaitanya Durbhakula, Manikya; ., . (International Journal of Engineering and Technology, 2018)
This paper introduces a reconfigurable Hairpin Bandpass Filter incorporated with PIN diode switching mechanism with good return loss and band pass characteristics for wireless communications.  The proposed filter consists of hairpin bandpass filter incorporated with switching mechanism placed over Arlon substrate with an effective dielectric constant of 2.2 and is designed to operate at two different resonant frequencies, i.e., at 1.75 GHz and 3.5 GHz independently by controlling the switching conditions of the PIN diodes. The filter is designed to offer a fractional bandwidth of 11% at 3.5GHz and 13% at 1.75GHz.  A proto type is fabricated and tested accordingly and the corresponding results are presented. The design is validated using the commercially available simulating software CST Microwave Suite and the results are compared with the measured values and a good agreement between them is obtained. The structure is better suitable for reconfigurability applications when attached to an antenna with the appropriate biasing network and finds many applications in wireless communication systems.